Energetics of Pfaffian–anti-Pfaffian domains - Simon, SH; Ippoliti, M; Zaletel, MP; Rezayi, EH (American Physical Society, 2020)
In several recent works it has been proposed that, due to disorder, the experimentally observed ν = 5/2 quantum Hall state could be microscopically composed of domains of Pfaffian order along with domains of anti-Pfaffian order. We numerically examine the energetics required for forming such domains and conclude that for the parameters appropriate for recent experiments, such domains would not occur.